A Multi-Step Transmission Electron Microscopy Sample Preparation Technique for Cracked, Heavily Damaged, Brittle Materials. (7th October 2014) - Weiss Brennan, Claire V.; Walck, Scott D.; Swab, Jeffrey J.
Abstract A new technique for the preparation of heavily cracked, heavily damaged, brittle materials for examination in a transmission electron microscope (TEM) is described in detail. In this study, cross-sectional TEM samples were prepared from indented silicon carbide (SiC) bulk ceramics, although this technique could also be applied to other brittle and/or multiphase materials. During TEM sample preparation, milling-induced damage must be minimized, since in studying deformation mechanisms, it would be difficult to distinguish deformation-induced cracking from cracking occurring due to the sample preparation. The samples were prepared using a site-specific, two-step ion milling sequence accompanied by epoxy vacuum infiltration into the cracks. This technique allows the heavily cracked, brittle ceramic material to stay intact during sample preparation and also helps preserve the true microstructure of the cracked area underneath the indent. Some preliminary TEM results are given and discussed in regards to deformation studies in ceramic materials. This sample preparation technique could be applied to other cracked and/or heavily damaged materials, including geological materials, archaeological materials, fatigued materials, and corrosion samples.